Transformative Islamic Spirituality as an Ethical Framework for Ecological Responsibility - Rozaq, Abdur; Zain, Moch Hibatullah (Yayasan Pesantren Mahasiswa An-Nur, 2024)
This article critically evaluates contemporary Islamic ecological piety and secular ecological ideologies to propose a spiritually enriched framework for meaningful environmental engagement. Employing a qualitative, philosophical-reflective methodology, it integrates conceptual analysis with comparative philosophical discussions between anthropocentric, ecocentric, and theocentric paradigms. The findings reveal significant shortcomings in current ecological practices, including superficiality within Islamic contexts and ideological limitations in secular ecologism. Although deep ecology offers insightful critiques against anthropocentric perspectives, its secular foundation limits practical implementation among religiously-oriented communities. Reflective insights from Islamic spirituality, notably the principles of tawhid and khalifah, are presented as practical ethical foundations for transformative ecological engagement. These concepts foster deep ecological consciousness and communal responsibility, enabling substantive rather than symbolic environmental actions. The study advocates integrating spiritual ethics within educational and religious institutions, exemplified by successful eco-pesantren models. This research contributes significantly by bridging spiritual and ecological ethics, suggesting practical approaches to ecological sustainability informed by Islamic spirituality, and encourages further empirical exploration into spiritually-based ecological frameworks.